THE EFFECT OF WATER SALINITY AND RESERVOIR TEMPERATURE ON SILICA DISSOLUTION DURING ASP FLOOD - ALRAHMAN AHMED, AHMED FATAH (2015)
Silica scale is one ofthe critical limiting factors that affects production wells during Alkaline-Surfactant-Polymer (ASP) flooding in sandstone reservoirs. The Injection of ASP slug in sandstone reservoir results in silica dissolution, which causes significant changes in porosity and permeability. In this study, aseries of static experiments were performed first to investigate the effect of brine salinity, brine hardness and ASP components on silica dissolution at different temperatures, using Berea sandstone samples. The changes in the sand mineralogy and silica content were identified using Scanning Electron Microscopy (SEM) attached to Energy Dispersive X-RAY (EDX) before and after saturation with various brine salinities. Thin section analysis was used also to examine the effect ofsilica dissolution on the surface ofslide core sample before and after saturation.